De Cor_po e (C)Alma: De Cor_po e (C)alma - Nunes, André (2025)
The cover image is composed of art works by artists and occupational therapists André Nunes and Mariangela Scaglione Quarentei. The image of André Nunes has been present in this dossier since its publication due to an invitation that considered the creative trajectory of this border artist.Mariangela Quarentei's poem "Palavra" brings out the complexity of words spoken, written, pronounced, thought. The dossier's editorial group decided to create this composition because we understand that the image, created in mixed media, together with the poem will open this issue without the need for text or other linguistic supports, composing a plane of intensity connected to the inspiring desire flows of this dossier.